Ethical Issues and Information Communication Technology (ICT) Use in the New Era - Otulugbu, Dumebi; Ogunobo, Marvelous-Mary (International Journal of Knowledge Content Development & Technology, 2022)
The new age is characterised with information communication technology, where computers, laptops, mobile gadgets such as palmtops, tablets, mobile phones and the internet have made their way to every sphere of life from our domestic environments such as our homes, small retail shops, banks to large industries and the world at large. Over time so many questions about the ethical use of the Information and Communication Technology (ICT) have emerged on who have access to what technology and the use of it and like every other technological invention, this paper will look at the morality involved in making use of ICT to promote ethical use of data or information in virtual environment. ICT also possesses both positive and negative impacts; the questions that these impacts raise are what this piece attempts to answer, providing global scrutiny to these ethical issues, situations and questions; and providing recommendations in line with global best practices.